Genome-Wide SNP Data Revealed Notable Spatial Genetic Structure in the Deep-Sea Precious Coral Corallium japonicum - Takata, Kenji; Iwase, Fumihito; Iguchi, Akira; Yuasa, Hideaki; Taninaka, Hiroki; Iwasaki, Nozomu; Uda, Kouji; Suzuki, Tomohiko; Nonaka, Masanori; Kikuchi, Taisei; Yasuda, Nina (Frontiers in Marine Science, 2021)
Estimating the spatial extent of gamete and larval dispersal of deep-sea coral species, is challenging yet important for their conservation. Spatial autocorrelation analysis is useful for estimating the spatial range of dispersal of corals; however, it has not been performed for deep-sea coral species using genome-wide single nucleotide polymorphisms (SNPs). In this study, we examined the spatial genetic structure of a deep-sea coral species—the Japanese red coral, Corallium japonicum, sampled off the coast of Kochi, which lies to the southwest of the Shikoku Island in Japan; the Kochi region suffers from over-harvesting because of its high commercial value. We also examined the power of detecting significant spatial genetic structure by changing the number of loci and the proportion of missing data using both de novo analysis and mapping analysis. Similar results were obtained for both de novo and mapping analysis, although a higher number of loci were obtained by the mapping method. In addition, “many SNPs with a lot of missing data” was generally more useful than “a small number of SNPs with a small amount of missing data” to detect significant fine-scale spatial genetic structure. Our data suggested that more than 700 neutral SNPs were needed to detect significant fine-scale spatial genetic structure. The maximum first distance class that can detect significant spatial genetic structure within Kochi for the C. japonicum population was less than 11 km, suggesting that the over-harvesting of C. japonicum within a diameter of approximately 11 km in the Kochi area should be avoided, because this can cause the local extinction of this species.